سيميائية العتبات النصية في شعر بغداد سايح سمفونية جرح بارد أنموذجا - برداوي, عمر (University of Eloued جامعة الوادي, 2022)
تعد العتبات النّصية نصوصا موازية لا تقل أهمية عن النّص المتن، لذلك أصبحت موضوع الاهتمام من قبل المبدعين والنّقاد على حد سواء لما تتميز به من قدرة على إنارة النّص الأدبي وتكريس أدبيته، أو تحقيق الإثارة وشدّ اهتمام المتلقي. ونحاول في هذا المقال رصد أهم العتبات النّصية في شعر بغداد سايح من خلال دراسة مجموعته الشّعرية سمفونية جرح بارد، وقد اتكأت مقاربتنا هذه على ما يتيحه لنا المنهج السّيميائي من إجراءات نراها مناسبة لرصد الدّلالات القريبة والبعيدة لهذه العتبات. Abstract: The Paratext are parallel texts that are no less important than the body text, so they have become the subject of interest by writers and critics alike due to their ability to clarify the literary text and show its literariness, or to achieve excitement and attract the reader's interest. We try in this article to monitor the most important Paratext in the poetry of Baghdad Sayeh through the study of his poetry group Symphoniyat Jorh Barid. Our approach is based on what the semiotic approach provides us with procedures that we consider appropriate to monitor semantics of these Paratext.